The Fiscal Abuse of Central Banks - Fry, Maxwell (IMF Working Papers; Working Paper, 1993)
This paper reviews the fiscal activities that governments in a sample of 26 developing countries have obliged their central banks to undertake. In the main, these activities fall under five categories: (1) collecting seigniorage; (2) imposing financial restriction; (3) implementing selective credit policies; (4) undertaking foreign exchange operations at nonmarket-clearing prices; and (5) providing implicit or explicit deposit insurance at subsidized rates and recapitalizing insolvent financial institutions. Not all central banks engage in all these activities, but some central banks perform additional fiscal activities such as collecting taxes and running food procurement programs.